Longitudinal changes in fasting plasma glucose are associated with risk of cancer mortality: A Chinese cohort study. (21st June 2021) - Wu, Mengyin; Lu, Jieming; Yang, Zongming; Shen, Peng; Yu, Zhebin; Tang, Mengling; Jin, Mingjuan; Lin, Hongbo; Chen, Kun; Wang, Jianbing
Abstract: Background: Numerous studies have suggested that fasting plasma glucose (FPG) was associated with the risk of mortality. However, relationship on longitudinal changes of FPG with the risk of mortality remained inconsistent. Methods: We examined the association of FPG at baseline and its longitudinal changes with risk of mortality based on a cohort study in Yinzhou, China, during 2010–2018. Cox regression models and competing risk models were separately used to examine the association of FPG levels and long‐term fluctuation with risk of total and cause‐specific mortality. Results: Subjects who had an impaired fasting glucose or diabetes suffered a higher risk of total mortality than subjects who had a normal fasting glucose (HRs and 95% CIs: 1.17 [1.01–1.35], 1.30 [1.10–1.53], respectively). The HR for total mortality was 1.54 (95% CI: 1.29–1.84) and for cancer mortality was 1.41 (95% CI: 1.04–1.92) in the highest quartile of coefficient of variation of FPG. Trajectory analysis indicated that subjects with a significantly changed FPG suffered a higher risk of total mortality. Conclusion: According to this cohort study, we found that long‐term fluctuation of FPG was significantly associated with the risk of total and cancer mortality. Our findings suggest that long‐term fluctuation of FPG could be used as an efficient indicator for predicting the subsequent risk of mortality. Abstract : Fasting plasma glucose variation could increase risk of cancer mortality. Controlling fasting plasma glucose fluctuations is of great health significance.